Phenomenology and Clinical Correlates of Stimulus-Bound Tics in Gilles de la Tourette Syndrome - Janik, Piotr; Milanowski, Lukasz; Szejko, Natalia (Frontiers in Neurology, 2018)
Introduction: Stimulus-bound tics (SBTs) belong to stimulus-induced behaviours and are defined as tics that occur in response to internal or external stimuli. The aim of the study was to assess the prevalence and associations of SBTs with other stimulus-triggered behaviours, premonitory urges and stimulus sensitization in Gilles de la Tourette syndrome (GTS). Methods: We performed a prospective, one-registration study in a cohort of 140 consecutive patients with GTS. Duration of GTS was 10.6±8.7 years (range: 0–39 years). SBTs were diagnosed during the interview. Results: SBTs occurred at some point in the lifetime of 20.7% of patients. The presence of SBTs in adults was four times as frequent as in children (35.5% vs 9.0%) with the most frequent onset in adolescence (58.8%) and adulthood (29.4%). These tics started 9.1±4.7 years after the onset of tics. One stimulus and mental stimulus preceded tics most frequently, 44.8% and 33.3%, respectively. There was no established pattern of tics triggered by stimuli. Multivariate logistic regression analysis showed significant associations of SBTs with age at evaluation, tic severity, and palilalia but not with any co-morbid psychiatric disorders. 80% of patients showed at least one stimulus-triggered behaviour. Premonitory urges and stimulus sensitization were reported by 60.0% and 40.7% of patients, respectively. No significant correlations between SBTs, premonitory urges and stimulus sensitization were found. Conclusion: SBTs are a part of the tic spectrum and should be taken into account by clinicians who deal with GTS patients. These tics fall at the tic end of the continuum of stimulus-induced